Weather /Climate Manual for Agriculture - Martey, Francisca (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Agriculture is an economic activity that produce food necessary for human livelihood and it is highly dependent upon weather and climate; however, agriculture is also likely to be very vulnerable to climate variability and change. Climate variability and climate change are the main causes of stress on food production and availability.